1998
DOI: 10.1046/j.1365-2672.1998.853540.x
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial effect of organic acids, sour dough and nisin against Bacillus subtilis and B. licheniformis isolated from wheat bread

Abstract: H. ROSENQUIST AND Å . H AN S EN . 1998. Prevention of growth in wheat bread for more than 6 d of approximately 10 6 rope-producing Bacillus subtilis spores per gram of dough was achieved by addition of propionic or acetic acids at levels of 0·10% v/w (based on flour weight), or by addition of 15% sour dough fermented with Lactobacillus plantarum C11, Lact. brevis L62, Lact. plantarum ('vege-start 60'), Lact. plantarum (ch 20), Lact. maltaromicus (ch 15), or the commercial sour dough starter culture, Lact. sanf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 43 publications
2
48
1
3
Order By: Relevance
“…According to our observations, the time of inhibition of rope symptoms increases at a low pH (range, pH 3.7 to 4.3). This finding differs from the observations of other authors that indicated that the ropeinhibiting pH values were 4.69 (39) and 4.8 (34). The differences may have been due to the different experimental conditions and the different strains used as indicators.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…According to our observations, the time of inhibition of rope symptoms increases at a low pH (range, pH 3.7 to 4.3). This finding differs from the observations of other authors that indicated that the ropeinhibiting pH values were 4.69 (39) and 4.8 (34). The differences may have been due to the different experimental conditions and the different strains used as indicators.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, rope-causing strains are also characterized by faster development and enhanced protease and amylase production during growth in the bread crumb (31). Current international trends towards elimination of chemical preservatives, including calcium propionate (34,35), which may cause cancer tumors (34), from bread and other foodstuffs is expected to increase the risk of bread spoilage by rope-producing Bacillus strains (4). The traditional sourdough fermentation in bread making allows natural acidification that is able to control rope spoilage.…”
mentioning
confidence: 99%
“…The ability of the spores to survive during baking (100°C for 15 to 60 min) and high amylase and protease activities have been identified as characteristics of strains of rope-forming bacilli (43,45). The acidification and production of organic acids by heterofermentative lactobacilli in sourdough prevents ropy spoilage of bread (43,44). However, the levels of organic acids in most bread varieties are too low to inhibit B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…Sourdough fermentations, as well as baking agents based on sourdoughs, have retained their importance in contemporary baking technology because of the improved aroma, texture, and shelf life of sourdough breads (7,35,40). The production of a wide variety of traditionally prepared baked goods continues to rely exclusively on the use of sourdough as a leavening agent.…”
mentioning
confidence: 99%